2020
DOI: 10.1155/2020/4543719
|View full text |Cite
|
Sign up to set email alerts
|

Shear Behavior and Anisotropy Characteristics of the Fracture Morphology of Sandstone with Different Water Contents

Abstract: Hydromechanical coupling in rock masses is an important issue for many rock mechanics and hydrogeology applications. The change of a water-bearing state will induce the fracture of the intact rocks and further accelerate the shear slip instability of the sheared surface. To investigate the weakening effect of water content on the mechanical properties of a rock mass, laboratory direct shear tests combined with three-dimensional analysis of sheared surfaces were carried out on sandstone samples with different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This, combined with the variation in the anisotropy of sample 2 during dehydration (Figure 3b) shows that the P-wave velocity of bedded sandstone is mainly controlled by the compactness of the bedding plane [37]. Many test results have also proven that the moisture content of rock has a great influence on the P-wave velocity perpendicular to the bedding direction, but a small influence on it in the parallel direction [6,38].…”
Section: Mechanism Of Dehydration Altering Anisotropy In Bedded Rocksmentioning
confidence: 99%
See 1 more Smart Citation
“…This, combined with the variation in the anisotropy of sample 2 during dehydration (Figure 3b) shows that the P-wave velocity of bedded sandstone is mainly controlled by the compactness of the bedding plane [37]. Many test results have also proven that the moisture content of rock has a great influence on the P-wave velocity perpendicular to the bedding direction, but a small influence on it in the parallel direction [6,38].…”
Section: Mechanism Of Dehydration Altering Anisotropy In Bedded Rocksmentioning
confidence: 99%
“…Anisotropy in rock structures leads to anisotropy in physical and mechanical properties, which can significantly affect the stability and safety of engineered structures such as underground chambers and rock slopes and should be considered in the design and construction processes [2][3][4]. Rocks exist in complex geological and hydrogeological environments and their moisture state are often in a dynamic state [5][6][7]. The moisture state has an important influence on the physical and mechanical properties of rocks [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tang [10] conducted uniaxial shear tests on coal rocks with different moisture contents and found that shear strength, shear displacement, cohesion, and internal friction angle all decrease with increasing moisture contents, which is described by the revised Mohr-Coulomb model for the case of water intrusion. Du et al [16] quantified the shear fracture surface morphology of sandstones with different moisture contents by using the variogram parameters, sill and range, and found that the distribution of water in the sample directly affected the initiation and propagation of cracks and fracture morphology characteristics. Liu et al [17] conducted systematic triaxial compression tests on three typical weakly cemented rocks (mudstone, sandstone, and sandy mudstone), and discussed the effects of confining pressure and moisture contents on rock mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%